Strategic Management of the Police Academy (Sekolah Polisi Negara) Polda Bengkulu in Enhancing Student Quality - Alamsya, Gafar; Asha, Lukman; Ifnaldi, Ifnaldi; Warlizasusi, Jumira; Fathurrochman, Irwan (Universitas Ahmad Dahlan, 2025)
Background. This study aims to explore and analyze the implementation of strategy management at the Police Academy (Police College) of Bengkulu Regional Police (SPN POLDA Bengkulu) in its efforts to improve student quality and its impact on graduate outcomes. The objective of this study is not only important for the development of education at the Bengkulu Regional Police Academy, but also contributes to a broader discourse on strategic management practices in other educational institutions. Therefore, these findings are expected to serve as a reference in decision-making and policy formulation aimed at improving the quality of education in law enforcement institutions. Methods. The methodology used in this study is descriptive qualitative with a case study approach. Data were obtained through observational interviews and document studies from 12 key informants over a period of three months (May-July 2023). Thematic analysis was conducted through coding and categorization, with data validity ensured through triangulation, member checking, and peer debriefing, as well as based on research ethics. This study aims to analyze and describe the implementation of strategic management in SPN administration, particularly in efforts to improve the competence and readiness of students as prospective police officers.Results. Research findings indicate that strategic management at the Bengkulu Regional Police Headquarters is implemented through focused vision and mission planning, strategic environmental analysis, and active leadership involvement in the decision-making process. These strategies have had a positive impact on the quality of graduates, as evidenced by improvements in professionalism, discipline, and operational readiness in task forces. Policy and strategy evaluations show that program implementation is relatively effective, although challenges remain in areas such as supervision and sustainability. Conclusion. This study recommends strengthening the monitoring system, continuing character development programs, and optimizing the role of instructors to further improve student quality.